2018
DOI: 10.3390/nu10060755
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Intestinal Manifestation of Celiac Disease in Children

Abstract: The aim of this literature review is to discuss the extra-intestinal manifestations of celiac disease within the pediatric celiac population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 78 publications
1
63
0
4
Order By: Relevance
“…The rash disappears with a GFD. This condition is however rare in children 85 . Interobserver variation between pathologists assessing the same intestinal biopsy specimens has been investigated and showed fair to substantial agreement 3,4 .…”
Section: Effects Of Celiac Disease In Bloodmentioning
confidence: 97%
See 2 more Smart Citations
“…The rash disappears with a GFD. This condition is however rare in children 85 . Interobserver variation between pathologists assessing the same intestinal biopsy specimens has been investigated and showed fair to substantial agreement 3,4 .…”
Section: Effects Of Celiac Disease In Bloodmentioning
confidence: 97%
“…There are many different manifestations of CD in children, and they are not confined to the small intestine 85 . Examples include short stature, delayed puberty, osteoporosis, liver and biliary disease, headaches, behavioural changes, and psychiatric disorders.…”
Section: Effects Of Celiac Disease In Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical presentation is broad and includes gastrointestinal upset, chronic fatigue, nutrient deficiencies, poor growth, and failure to thrive. Extra-intestinal manifestations are common, and while they were once considered more frequent in adults than children with CeD, recent data suggests the frequency is similar in CeD children, although the types and rates of recovery differ ( 8 ). In children, extra-intestinal manifestations include short stature, anemia, delayed puberty, dental enamel hypoplasia, reduced bone density, oral ulcers, liver and biliary disease, and dermatitis herpetiformis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have shown that CD should be investigated in patients with autoimmune thyroid disease, dermatitis herpetiformis, type 1 diabetes and irritable bowel syndrome (6)(7)(8)(9). The most common extra-intestinal symptom in children is growth retardation and iron deficiency anemia in adults (10). Although CD is a gastrointestinal disease with small intestinal mucosal lesion, small intestinal mucosal damage develops gradually during the course of the disease and mucosal deterioration can take many years.…”
Section: Introductionmentioning
confidence: 99%